Contesting Urban Space Transformation in Semarang: A Study of the Simpang Lima Area from 1975-2000 - Widiantoro, Sulton; Wijayati, Putri Agus (Journal of Indonesian History, 2024)
This article examines the contestation of urban space in the Simpang Lima area of Semarang from 1975 to 2000 through the perspective of Henri Lefebvre's theory of The Production of Space. Initially designed as a public space for social and cultural activities, Simpang Lima experienced a struggle for space involving the government, private sector, and the community. This study explores how the shift in government policies prioritized public interests, leading to the commercialization of spaces. This transformation was marked by the replacement of public facilities such as sports arenas and meeting halls with commercial buildings like malls and hotels. The impacts of this spatial contestation included the removal of public facilities, the emergence of the informal sector, and increased economic activity. The contestation of space in Simpang Lima highlights the power struggle among various stakeholders, including government authorities, private investors, and the local community. The findings reveal that while commercialization brought economic benefits, it also resulted in social exclusion and the loss of cultural identity. This study emphasizes the transformation of public spaces into private spaces due to the lack of government support for public interests, ultimately benefiting the private sector economically.